2016
DOI: 10.1016/j.neulet.2016.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of LMW and HMW FGF2 against amyloid beta toxicity in primary cultured hippocampal neurons

Abstract: Basic Fibroblast growth factor (FGF2) is important in development and maintenance of central nervous system function. Studies have demonstrated that low molecular weight (LMW) FGF2 is a neuroprotective factor against various insults in vivo and in vitro. In the present study we investigated the neuroprotective effects of high molecular weight (HMW) and LMW FGF2 against amyloid beta-induced neurotoxicity. The results showed that both LMW and HMW FGF2 attenuated the amyloid beta toxicity in the primary cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
(40 reference statements)
1
13
0
3
Order By: Relevance
“…Our data further indicate that both FGF-2 isoforms also similarly increase AKT and ERK phosphorylation in the brain. The AKT and ERK signaling pathways were shown to be involved in the ability of HMW FGF-2 to ameliorate depressive symptoms in the CUMS model, which was consistent with a previous study showing that AKT and ERK were similarly activated in neurons by HMW and LMW FGF-2 ( Cheng et al, 2016 ). The present report is the first to show that ERK and AKT pathway activation, Bcl-2 upregulation and caspase-3 inhibition are all required for HMW FGF-2 to improve depressive symptoms in mouse models of non-hereditary depression.…”
Section: Discussionsupporting
confidence: 90%
“…Our data further indicate that both FGF-2 isoforms also similarly increase AKT and ERK phosphorylation in the brain. The AKT and ERK signaling pathways were shown to be involved in the ability of HMW FGF-2 to ameliorate depressive symptoms in the CUMS model, which was consistent with a previous study showing that AKT and ERK were similarly activated in neurons by HMW and LMW FGF-2 ( Cheng et al, 2016 ). The present report is the first to show that ERK and AKT pathway activation, Bcl-2 upregulation and caspase-3 inhibition are all required for HMW FGF-2 to improve depressive symptoms in mouse models of non-hereditary depression.…”
Section: Discussionsupporting
confidence: 90%
“…These pathways mediate FGF2's function. For example, FGF2-induced glutamate release (Numakawa et al, 2002) and axonal branching (Abe et al, 2001) are mediated by MAPK/ERK signaling, and FGF2 neuroprotective effects against amyloid ␤ toxicity in cultured hippocampal neurons are mediated through PI3K/AKT signaling (Cheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that these functions of LMW or HMW FGF-2 were mediated by activating FGFR1. FGF-2 is known to activate ERK and AKT signaling pathways (Cheng et al, 2016). Here, we showed that treatment of astrocytes with LMW and HMW FGF-2 for 30 min both resulted in increased phosphorylation of ERK, AKT (Ser473) and GSK-3β compared with the control group ( Figure 4A).…”
Section: Lmw Fgf-2 Promotes Astrocyte Proliferationmentioning
confidence: 69%